The Instagrammable outdoors – Investigating the sharing of nature experiences through visual social media. Issue 6 (29th June 2021) - Arts, Irma; Fischer, Anke; Duckett, Dominic; van der Wal, René
Abstract: Despite the growing popularity of Instagram as a medium to portray nature and the outdoors, there remains limited research available exploring its influence on people's experiences in nature. We investigate Instagram as a three‐way negotiation between users, the platform's affordances and social norms associated with both Instagram use and outdoor experiences. Moving beyond polarized, conceptual debates situating social media affordances within dystopias and eutopias, we provide empirical insight from the lived experiences of everyday Instagram users reflecting upon their mediated outdoor activities. We found that participants shared special moments, beautiful landscapes and happy memories while they struggled with notions of authenticity associated with these experiences. They perceived certain scenes as more 'Instagrammable' than others, and this led to sharing homogenous stories and visual representations of the outdoors. At the same time, participants actively reflected on this standardization and aestheticization of the landscape and their experiences, and highlighted strategies to counter this, such as actively following voices normally under‐represented in media portraying outdoor activities or posting pictures that were not 'polished'. We conclude that to understand modern‐day interactions with nature and move beyond purely theoretical discussions about the flaws or merits of social media, we need to look at users' own strategies that integrate visual social media into their outdoor activities, while taking into account how platform features and social norms contribute to the construction of these activities. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.